2015
DOI: 10.1021/acs.jpcb.5b06228
|View full text |Cite
|
Sign up to set email alerts
|

Weak Micelle-Like Aggregation in Ternary Liquid Mixtures as Revealed by Conductivity, Surface Tension, and Light Scattering

Abstract: A very small concentration of NaBr is added to ternary, transparent, and thermodynamically stable mixtures of water, ethanol, and octanol. Measuring the electrical conductivity along lines with constant water to ethanol ratios reveals remarkable composition dependencies similar to those found in classical surfactant-based microemulsions. Indeed, light-scattering experiments along the same composition lines and additional surface tension measurements confirm the onset of aggregation and possibly direct, biconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…However, due to the lack of the surfactant, conductivity enhances only within one order of magnitude. The molecule forming the interface between water droplets and the citronellol-rich surrounding medium has been found in previous studies 2,9 unequivocally as being ethanol, and according to that in the systems studied here, the ethanol is the main component of the interfacial film whenever microstructures are present. As shown in Figure 3a, the low conductivity below φ w p suggests that the reverse droplets are discrete (isolated droplets in a non-conducting citronellol medium, forming w/o microemulsion) and show rare interaction.…”
Section: Electrical Conductivity Measurements and Microregions Of supporting
confidence: 83%
See 1 more Smart Citation
“…However, due to the lack of the surfactant, conductivity enhances only within one order of magnitude. The molecule forming the interface between water droplets and the citronellol-rich surrounding medium has been found in previous studies 2,9 unequivocally as being ethanol, and according to that in the systems studied here, the ethanol is the main component of the interfacial film whenever microstructures are present. As shown in Figure 3a, the low conductivity below φ w p suggests that the reverse droplets are discrete (isolated droplets in a non-conducting citronellol medium, forming w/o microemulsion) and show rare interaction.…”
Section: Electrical Conductivity Measurements and Microregions Of supporting
confidence: 83%
“…Moreover, changes of slopes are also found when evaporation rates are plotted versus the amount of oil phase during the transition from o/w to w/o domains, a phenomenon that is widely used in formulation of long-lasting perfume formulation. 2 According available literature only few recent studies reported the theoretical analysis based on the percolation phenomenon, which occurs as the microstructure of microemulsions changes. [3][4][5][6] Recently, the static and dynamic percolation models have been proposed for describing the mechanism of percolation.…”
Section: Introductionmentioning
confidence: 99%
“…as thermal fluctuations [8][9][10][11]14 . For water(1)-ethanol(2)octanol (3), results of molecular dynamics simulation 8,11 lead to rough estimatations, n(G 0 13 − G 0 23 ) = 100 − 300, −g 3 = 20 − 60, and g 2 3 nχ = 300 − 3000, at X = 0.2.…”
Section: Bmentioning
confidence: 99%
“…In water-alcohol solvents, nanometer-sized solute-rich aggregates preexist with alcohol molecules covering them in one-phase states [8][9][10][11]13 . Then, they should play the role of embryos of critical liquid droplets consisting of solute and alcohol molecules.…”
Section: E Solute-induced Nucleationmentioning
confidence: 99%
“…Thus, we can observe a bell-shaped conductivity curve with a maximum for a concentration in ethanol of about 60 % in weight fraction. If we refer to other works relative to conductivity measurements in the pre-ouzo region [32], we really have to consider the presence of two pseudo-phases to explain such behavior.…”
Section: Conductivity Measurementsmentioning
confidence: 99%